Los tabúes y prejuicios de la sexualidad en la población urbana y rural. - Ordoñez Morocho, Rosa; Chevez Roque, Nicole Ibeth; Gordillo Quizhpe, Marco Ivan (Universidad Técnica de Machala, 2022)
Sexual taboos when conceived historically and culturally as something for-bidden and sacred, appeals to the ignorance of people and society, even pu-nished and in a certain way regularized by social norms, which establishes relatively between what is correct and incorrect. The church is a social in-hibitor of freedom and sexual behavior, forgetting that the human being is a sexual being according to Freud. Sexual behaviors are typical of human biology as are desires, masturbation and virginity, however, when are made, biological, social, cultural, ethical and religious factors are involved by ta-boos, get disenchanted and lose their nature. Prevailing in postmodernity that man is the one with sexual freedom against women who would call it im-moral. This research was based on the mixed approach, with reference to the social sciences, in which reference frames were used and the discussion with data related to facts approach through observation and statistics generated from direct sources. A comparative analysis of populations differentiated in cultural contexts was carried out, by establishing that virginity is a guaran-tee of purity and fidelity in marriage, but not in the other group, it does not establish it as a determining factor in the formation of a couple. Likewise, freedoms and sexual attachment respond to the human condition and with a certain restriction to religious beliefs and values.
Los tabúes sexuales al concebirse histórica y culturalmente como algo prohibido y sagrado, apela a la ignorancia de las personas y la sociedad, incluso castigado y en cierta forma regularizados por las normas sociales, que establece relativamente entre lo que es correcto e incorrecto. La iglesia es un actor inhibidor social de las libertades y conductas sexuales, olvidándose que el ser humano es un ser sexuado de acuerdo a Freud. Las conductas sexuales son propias de la biología humana, como lo son los deseos, pensamientos y relaciones sexuales, la masturbación y la virginidad, sin embargo, al momento de efectuarse, intervienen factores biológicos, sociales, culturales, éticos y religiosos, que, al envolverlas por los tabúes, se desencantan y pierden su naturaleza. Prevaleciendo en la posmodernidad que el hombre es el que tiene mayores libertades sexuales frente a la mujer calificándola de inmoral. La investigación se basó en el enfoque mixto, con referencia a las ciencias sociales, en la que se hizo uso de marcos referenciales y la discusión con datos relativos a hechos abordados mediante la observación y estadísticas generadas a partir de fuentes directas. Se realizó un análisis comparativo de poblaciones en contextos culturales diferenciados, al establecerse que la virginidad es garantía de pureza y fidelidad en el matrimonio, no así el otro grupo, no lo consagra como un factor determinante en la conformación de una pareja. Así mismo las libertades y el apego sexual, responden a la condición humana y con cierta restricción a creencias y valores religiosos.
Keywords: SEXUALIDAD; TABÚES; SOCIEDAD; POBLACIÓN URBANA